FAKTOR-FAKTOR YANG MEMENGARUHI CREDIT RISK-TAKING PADA PERUSAHAAN PERBANKAN - Reisa Dyasvaro Zulanda Putri (STMIK Pringsewu, 2022)
Risk-taking is an activity that a bank takes for giving credit to the public to increase their profit. Risks occur because of the uncertainty condition taken by the company. The sample will be limited to 28 banks located and listed in Bursa Efek Indonesia (BEI) over the period 2013-2017. The main data source of all the variable is financial statements, annual reports, ICMD (Indonesian Capital Market Directory) and the official website of bank in 2013-2017. The conclusion of this study is to create the model which significantly related to bank risk-taking. There is 4 method to examine the best model. The methods are forward method, backward method, stepwise method and enter method. R-squared, adjusted R-squared, AIC, SIC, and Cp Mallows are the criterion for choosing the best model in each method. At the end of this study, there is a final regression model that shows all the significant variable which can explain bank risk-taking. Determinants of bank risk-taking variable in this study are bank capital, bank size, mergers and acquisitions, bank ownership, off-balanced sheet, LDR, BI rate, inflation, and GDP Growth.